The Relationship of Employee Characteristics towards Knowledge of the Evacuation Route Utilization - Atika Ayu Kriswijayanti; Mulyono Mulyono (Universitas Airlangga, 2021)
Introduction: A hospital as a health service facility needs to provide safe infrastructures, especially during disasters. The evacuation route is a safety support facility that can be used by everyone. A previous study states that when disasters occurred, nurses in the hospital did not know how to evacuate due to the difficulty in accessing the evacuation route. This study aims to analyze the relationship between the employee characteristics and knowledge of the evacuation route utilization. Methods: The study used an inferential analytical quantitative method. The population in this study was 178 temporary employees. The stratified random sampling technique was used to gain a sample of 64 people. The variables analyzed in this study were age, work period, education level, training, and knowledge of the temporary employees. Moreover, questionnaires were filled by the temporary employees as a technique of data collection. The Chi-Square test was used as the technique of data analysis. Results: The results of the study show that in the highest number, 40.6% of the employees are 31-40 years old, 56.3% of the employees have 1-10 years of service, 39.1% of the employees have a diploma degree, and 65.6% of the employees have participated in the evacuation route training.In addition,based on the bivariable analysis, the authors find that there is a relationship between employees’ age and knowledge (p value = 0.036), work period (p value = 0.039), education level (p value = 0.029), and training (p value = 0.029). Conclusion: There is a relationship between the employee characteristics and knowledge regarding the evacuation route utilization.Keywords: disasters, employees, evacuation route, hospitals, knowledge Keywords: disasters, employees, evacuation route, hospitals, knowledge